Efficacy of Tulsi (Ocimum Sanctum) Plant Powder on Health, Growth and Carcass Traits of Japanese Quail (Coturnix Japonica) - Naeem,H (2022)
ABSTRACT The objective of the current work was to assess the effects of Tulsi plant powder on the health, growth and carcass characteristics of Japanese quail. In total, 300 quails (1-week old) were distributed into four treatment groups with five replicates each. The first group (T0) was a control group where a basal standard diet was offered to the birds. Groups T0.5, T1 and T1.5 were supplemented with Tulsi plant powder at a rate of 0.5%, 1%, 1.5%, respectively. Data were analyzed in SPSS software by applying one-way ANOVA and significant and notable means were analyzed through Duncan’s New Multiple Range Test. Dietary supplementation of T1.5 significantly (p≤0.05) increased the feed intake, body weight, gain in weight and presented a better feed conversion ratio. Significantly higher glucose, total cholesterol, HDL, WBCs, RBCs and HCT were observed in the quails from T1 than in the control group (p≤0.05). However, the quails from T1.5 had significantly (p≤0.05) higher hemoglobin, MCV, platelets and total protein contents. On the other hand, the T0 group was only higher in LDL contents. Non-significant (p>0.05) in MCH, MCHC, triglyceride, VLDL were noted among the experimental groups. It was concluded that the dietary supplementation of Tulsi plant powder at 1.5 % is beneficial for improving the growth performance and can be used in the diet of Japanese quail without compromising the health status and carcass traits.